Design and preparation of three-dimensional MnO/N-doped carbon nanocomposites based on waste biomass for high storage and ultra-fast transfer of lithium ions. Issue 40 (2nd October 2018) - Feng, Qiaoxia; Li, Huanxin; Tan, Zhong; Huang, Zhongyuan; Jiang, Lanlan; Zhou, Haihui; Pan, Hongyu; Zhou, Qiang; Ma, Shuai; Kuang, Yafei
Abstract : Batteries with fast charging capability are urgently needed to meet the rapidly increasing demand for energy storage devices. Abstract : Batteries with fast charging capability are urgently needed to meet the rapidly increasing demand for energy storage devices. For a lithium-ion battery (LIB), the anode materials hinder the realization of fast charging. Herein, we report a three-dimensional (3D) MnO nanoparticle (NP) N-doped lychee exocarp flaky carbon (MnO@NLEFC) based on biomass waste lychee exocarp for ultra-fast chargeable LIB anode materials. The rational design of using the redox reaction of lychee exocarp (cellulose, hemicellulose, lignin, etc. ) and KMnO4 to generate a large number of MnO x nanoparticles on the surface of the lychee exocarp and then pyrolysis with the supplemented nitrogen source melamine can successfully realize the preparation of three-dimensional MnO@NLEFC. MnO nanoparticles inlaid in the carbon-based material not only improve the storage capacity of Li +, but also significantly increase the spacing of carbon layers and the disordered degree of carbon, which largely reduces the resistance for Li + migration and thereby accelerates the rates of insertion and extraction of Li + . Due to these factors, MnO@NLEFC exhibits a high reversible capacity of 515.5 mA h g −1 after 1000 cycles at 2 A g −1 as the anode for a Li-ion battery. Even at an ultra-high current density of 20 A g −1, it can still deliver a high reversible capacity of 309.2 mA h g −1 after 1000 cycles with an efficiency over 95%, showing superior fast-charging capability.